1992
DOI: 10.1063/1.462878
|View full text |Cite
|
Sign up to set email alerts
|

State-to-state rotational energy-transfer measurements in the v2=1 state of ammonia by infrared–infrared double resonance

Abstract: An infrared double-resonance laser spectroscopic technique is used to study state-resolved rotational (R–R, R–T) energy transfer in ammonia (14NH3) (self-collisions and between ammonia and foreign gases). NH3 molecules are prepared in selected rovibrational states of the v2=1 level using coincidences between CO2 -laser lines and ν2 fundamental transitions. Measurements of both the total rate of depopulation by collisions, and the rates of transfer into specific final rovibrational states (v,J,K) have been carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…with i X an angular factor calculated in [45], ba the Einstein coefficient, b the degeneracy factor of the upper level and ± a geometrical factor equal to ½ for a Gaussian laser beam (assumed here with a ~5 mm waist) and to 1 in the limit of a homogeneous power over the whole transverse laser beam profile [44]. Under typical experimental conditions (~1 Pa), 1 2 2 = 120 kHz (see Table 1) and 1 is estimated to be 25% of 2 [46,29].…”
Section: Saturation Of the Molecular Transition And The Impact On Detmentioning
confidence: 99%
“…with i X an angular factor calculated in [45], ba the Einstein coefficient, b the degeneracy factor of the upper level and ± a geometrical factor equal to ½ for a Gaussian laser beam (assumed here with a ~5 mm waist) and to 1 in the limit of a homogeneous power over the whole transverse laser beam profile [44]. Under typical experimental conditions (~1 Pa), 1 2 2 = 120 kHz (see Table 1) and 1 is estimated to be 25% of 2 [46,29].…”
Section: Saturation Of the Molecular Transition And The Impact On Detmentioning
confidence: 99%
“…Beyond state-to-state experiments [41][42][43] averaged quantities such as the average energy transferred in a collision (< DE > ) have been measured in cases where the density of states of the highly excited molecules was too large for state specific probing of quantum states. [44,45] Recently, it has been shown that the technique of kinetically controlled selective ionisation (KCSI) developed by Luther et al [46] can provide moments of energy transfer (< DE > , < DE 2 > ), as well as energy transfer transition probabilities PA C H T U N G T R E N N U N G (E',E) for highly excited molecules [47,48] at high densities of states.…”
Section: Molecular Collisional Energy Transfer At Low Temperaturesmentioning
confidence: 99%
“…The asQ (5,4) transition in the 2 fundamental band was pumped, while the (a) saR (6,4), and the (b) saR (7,4) transitions in the 2 2 4 2 hot band were scanned. The lineshape with the larger transferred spike was obtained when the pump and probe beams had perpendicular planes of polarization.…”
Section: Fig 12 Double-resonance Lineshapes Formentioning
confidence: 99%